2004
DOI: 10.1172/jci19684
|View full text |Cite
|
Sign up to set email alerts
|

Annexin II regulates fibrin homeostasis and neoangiogenesis in vivo

Abstract: A central tenet of fibrinolysis is that tissue plasminogen activator-dependent (t-PA- dependent) conversion of plasminogen to active plasmin requires the presence of the cofactor/substrate fibrin. However, previous in vitro studies have suggested that the endothelial cell surface protein annexin II can stimulate t-PA-mediated plasminogen activation in the complete absence of fibrin. Here, homozygous annexin II-null mice displayed deposition of fibrin in the microvasculature and incomplete clearance of injury-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
292
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 338 publications
(305 citation statements)
references
References 56 publications
13
292
0
Order By: Relevance
“…CD105 (Endoglin) was a member of transforming growth factor β (TGFβ) superfamily, Related to angiogenesis and maintaining vascular. CD105was highly expressed on endothelial cells of nascent tumor blood vessels and vascular endothelial cells of the tumor margin and was considered to be an ideal target in tumor therapy to inhibit tumor angiogenesis (Li et al, 2014), CD105 strongly overexpressed in the endothelial cells of arteries and veins surrounding tumor tissues contrasted with tumor cell (Ling et al, 2004), Our experiment confirmed CD105 is mainly expressed in the vascular endothelial cells around tumor tissues. Microvessel density (MVD) in tumor tissues is directly correlated with the prognosis of patients with cancer, some research showed that in breast cancer, cervical cancer and other malignant tumor tissues, MVD labeled by CD105 is better than that labeled by CD34, Ⅷ factor related antigen, Etc.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…CD105 (Endoglin) was a member of transforming growth factor β (TGFβ) superfamily, Related to angiogenesis and maintaining vascular. CD105was highly expressed on endothelial cells of nascent tumor blood vessels and vascular endothelial cells of the tumor margin and was considered to be an ideal target in tumor therapy to inhibit tumor angiogenesis (Li et al, 2014), CD105 strongly overexpressed in the endothelial cells of arteries and veins surrounding tumor tissues contrasted with tumor cell (Ling et al, 2004), Our experiment confirmed CD105 is mainly expressed in the vascular endothelial cells around tumor tissues. Microvessel density (MVD) in tumor tissues is directly correlated with the prognosis of patients with cancer, some research showed that in breast cancer, cervical cancer and other malignant tumor tissues, MVD labeled by CD105 is better than that labeled by CD34, Ⅷ factor related antigen, Etc.…”
Section: Discussionsupporting
confidence: 69%
“…In consequence of Annexin A2 could promote new blood vessels endothelial cells to form tube-like structure (Kumar et al, 1999;Ling et al, 2004), resulted in decrease of isolated vascular endothelial cells and lower MVD in specimens of strong positive (3+) Annexin A2 staining, Of course, the specific reason and mechanism needed further research.…”
Section: Discussionmentioning
confidence: 99%
“…RPE-J cells were cultured as described previously (Finnemann, 2003). Wild-type and annexin A2 null mutant mice (Ling et al, 2004) were maintained on a regular diet of food and water ad libitum, in accordance with UK Home Office regulations. Mice were killed by cervical dislocation and immediately enucleated.…”
Section: Cell Culture and Micementioning
confidence: 99%
“…In addition, arterial injury in A2 Ϫ/Ϫ mice is followed by a 2-fold increase in thrombotic vascular occlusion with an equivalent reduction in blood flow recovery (9). Third, injury-induced carotid artery thrombosis in rats can be averted by pretreatment with recombinant A2 (10).…”
mentioning
confidence: 99%
“…Ϫ/Ϫ microvascular endothelial cells lack t-PA cofactor activity, and the fibrin content of highly perfused A2 Ϫ/Ϫ tissues is ϳ2-fold greater than that observed in wild type controls (9). In addition, arterial injury in A2 Ϫ/Ϫ mice is followed by a 2-fold increase in thrombotic vascular occlusion with an equivalent reduction in blood flow recovery (9).…”
mentioning
confidence: 99%